Zenglibao : an internet money market fund run by Tianhong Asset Management Co., Ltd. - McFarlan, F. Warren (Franklin Warren); Jin, Yongjun; Li, Xiaohui ([London] : SAGE, 2016)
Tianhong Asset Management Co. issued its first quarter report on April 18, 2014. The report announced that the shares of its Tianhong Zenglibao Money Market Fund (Zenglibao Fund) were owned by 81 million individual investors and the value of these shares exceeded 541.3 billion Yuan; the profit in the first quarter was 5.7 billion Yuan. This book profiles the the Zenglibao Fund, well-known for its associated internet asset management platform Yu'ebao.
Originally Published in: McFarlan, Yongjun, J., & Xiaohui, L. (2014). Zenglibao: An Internet Money Market Fund Run by Tianhong Asset Management Co., Ltd. 4-214-311. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Tianhong Asset Management (Firm); Financial services industry -- China -- Case studies; Internet banking -- Case studies